Modelagem numérica de pilares mistos tubulares circulares preenchidos com concreto de alta resistência - Mariana da Conceicao Alcantara (2017)
The recent inclusion of high-strength concrete in the Brazilian standard ABNTN BR6 118:2014 tends to contribute to its wide use, including composite structures. Due to the disregard of this material by ABNTN BR 8800:2008 and even by international standards, newer search be comes necessary to verify the influence of the increasing strength in the behavior of composite structures of steel and concrete. In this context, the objective of the present work was to develop a nite element model to evaluate the bearing capacity and structural behavior of composite columns consisting of circular steel tubes lled with high-strength concrete. The numerical analysis was carried out through ABAQUS commercial software. Nonlinear mathematical models were selected to describe the stress-strain diagram of the materials, which included the connement effect of concrete. Other aspects of the numerical model development are described in this work, including the discretization of the nite element mesh, the modeling of the interface between steel and concrete and the simulation of the boundary and loading conditions. The validation of the nite element model was performed from results of axial and eccentric compression tests found in the literature. A parametric study was conducted to verify the inuence of some parameters on the bearing capacity and behavior of high-strength concrete-lled steel tube circular columns, namely: steel tube diameter and thickness, relative slenderness and concrete compressive strength. The bearing capacity obtained numerically in this step was compared to the values predicted by ABNT NBR 8800:2008, EN 1994-1-1:2004 and ANSI/AISC 360-16. It was veried that the numerical model underestimated the axial capacity of the high-strength concrete-lled steel tube circular columns possibly due to the high member imperfection adopted. ABNT NBR 8800:2008 and ANSI/AISC360-16 standards provided the high stand lowest values of bearing capacity respectively. The inclusion of the concrete compressive strength reduction factor in the ABNT NBR 8800:2008 standard, made its results safer, close to those obtained by the formulation of EN 1994-1-1:2004.